Impact of use of optical surface imaging on initial patient setup for stereotactic body radiotherapy treatments - Leong, Brian (J Appl Clin Med Phys, 2019)
PURPOSE: To evaluate the effectiveness of surface image guidance (SG) for pre‐imaging setup of stereotactic body radiotherapy (SBRT) patients, and to investigate the impact of SG reference surface selection on this process. METHODS AND MATERIALS: 284 SBRT fractions (SG‐SBRT = 113, non‐SG‐SBRT = 171) were retrospectively evaluated. Differences between initial (pre‐imaging) and treatment couch positions were extracted from the record‐and‐verify system and compared for the two groups. Rotational setup discrepancies were also computed. The utility of orthogonal kVs in reducing CBCT shifts in the SG‐SBRT/non‐SG‐SBRT groups was also calculated. Additionally, the number of CBCTs acquired for setup was recorded and the average for each cohort was compared. These data served to evaluate the effectiveness of surface imaging in pre‐imaging patient positioning and its potential impact on the necessity of including orthogonal kVs for setup. Since reference surface selection can affect SG setup, daily surface reproducibility was estimated by comparing camera‐acquired surface references (VRT surface) at each fraction to the external surface of the planning CT (DICOM surface) and to the VRT surface from the previous fraction. RESULTS: The reduction in all initial‐to‐treatment translation/rotation differences when using SG‐SBRT was statistically significant (Rank‐Sum test, α = 0.05). Orthogonal kV imaging kept CBCT shifts below reimaging thresholds in 19%/51% of fractions for SG‐SBRT/non‐SG‐SBRT cohorts. Differences in average number of CBCTs acquired were not statistically significant. The reference surface study found no statistically significant differences between the use of DICOM or VRT surfaces. CONCLUSIONS: SG‐SBRT improved pre‐imaging treatment setup compared to in‐room laser localization alone. It decreased the necessity of orthogonal kV imaging prior to CBCT but did not affect the average number of CBCTs acquired for setup. The selection of reference surface did not have a significant impact on initial patient positioning.